Engage less, provide more: Community health workers’ perspectives on how to overcome opposition to polio vaccination in Pakistan - Arman Majidulla; Marium A. Sultan; Ayesha Zaman; Muhammad Shafique; Saeed Ahmed; Farah Naz; Sadaf Nayyab; Ali Sohail (Global Public Health)
Pakistan has 40 Super High Risk Union Councils (SHRUCs) where polio has been persistently endemic, and community relationships have been a persistent challenge due to campaign fatigue and violent, organised resistance. This study aimed to gather perspectives from frontline workers in these areas to improve community engagement. We conducted participant observation, over 100 interviews, and held Human-centred Design inspired sessions with 171 teams of frontline polio staff from 2020 to 2022 in the SHRUCs of a major city in Pakistan. The results show that frontline polio workers repeatedly visited households broadly neglected by government services in SHRUCs, but some households refused the vaccine due to fatigue from multiple visits and fear of government surveillance. Others refused the vaccine to draw attention to their more pressing needs. Frontline polio workers suggested that decreasing touchpoints and providing additional services, such as food, medicines, primary health care, and sanitation services, would improve vaccine uptake. We discuss several implications for vaccine communications, including the importance of quality engagement, the legitimacy of rumours surrounding vaccination, the limited applicability of ‘vaccine hesitancy’, and the critical role of service provision in improving vaccine acceptability.